2014
DOI: 10.1111/gwat.12240
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Natural Losses of LNAPL Using CO2 Traps

Abstract: Efflux of CO2 above releases of petroleum light nonaqueous phase liquids (LNAPLs) has emerged as a critical parameter for resolving natural losses of LNAPLs and managing LNAPL sites. Current approaches for resolving CO2 efflux include gradient, flux chamber, and mass balance methods. Herein a new method for measuring CO2 efflux above LNAPL bodies, referred to as CO2 traps, is introduced. CO2 traps involve an upper and a lower solid phase sorbent elements that convert CO2 gas into solid phase carbonates. The so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 29 publications
2
43
0
Order By: Relevance
“…The presence of distinct microbial phylotypes in the contaminated core as compared to the clean core, coupled with recently published data indicating that hydrocarbon degradation is actively occurring at the site studied herein (McCoy et al 2014). provides evidence linking observed microbial phylotypes with hydrocarbon degradation processes within the LNAPL body.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The presence of distinct microbial phylotypes in the contaminated core as compared to the clean core, coupled with recently published data indicating that hydrocarbon degradation is actively occurring at the site studied herein (McCoy et al 2014). provides evidence linking observed microbial phylotypes with hydrocarbon degradation processes within the LNAPL body.…”
Section: Discussionsupporting
confidence: 76%
“…Toluene was not detected in any of the soil or water samples (305 samples assayed). The relatively low levels of GRO and absence of toluene, combined with recently published data showing higher CO 2 fluxes at grade compared to nearby uncontaminated locations (McCoy et al 2014). indicated ongoing microbial degradation.…”
Section: Geochemical Characterization Of the Lnapl Bodymentioning
confidence: 58%
See 1 more Smart Citation
“…NSZD describes the natural loss of LNAPL due to dissolution, volatilization, and most importantly, biodegradation (ITRC ). Over the last several years, studies have shown that NSZD rates are on the order of 100s to 1000s of gallons per acre per year (Sihota et al ; McCoy et al , Palaia, 2016; Garg et al ).…”
Section: Digital Innovation In Site Monitoringmentioning
confidence: 99%
“…Closed-system flux chambers and gas flux models have been used to determine net respiration in contaminated soils 12,13,[15][16][17] . In these studies, spatial measurements directly associated with a contaminant plume and with background areas showed enhanced biodegradation of organic contaminants.…”
Section: Introductionmentioning
confidence: 99%